Analysis of the role of fisherwomen from TPI Untia Makassar City in sustainable fisheries development - Muh Yusran; Muhammad Sabiq; Hasbi Hasbi; Sakaria Sakaria (Sekolah Tinggi Ilmu Pertanian Wuna, 2022)
The role of women in the fisheries sector is often neglected, even though women in coastal areas and fishery areas, such as ponds and TPI, almost dominate. The purpose of this study was to analyze the role of fisherwomen in TPI Untia Makassar City in the development of sustainable fisheries. The research was conducted from September to October 2021, in the community of fisherwomen at TPI Untia, Makassar City. The type of data collected in this study is primary data. The method used to collect or obtain data is a survey method with interview techniques. The sampling technique used is the purposive sampling technique. The results of the factor analysis showed that the five variables studied to describe the role of fisherwomen from TPI Untia Makassar City in the development of sustainable fisheries were declared feasible and valid with a correlation value of 0.735. The five variables are divided into 2 factors (components), namely; factor 1, which includes; variable economic role, social role, and domestic role. While factor 2 which includes; participatory and institutional variables.